1983
DOI: 10.1002/ijc.2910310502
|View full text |Cite
|
Sign up to set email alerts
|

Formation and growth of multicellular spheroids of human origin

Abstract: Different types of human cells which normally grow as monolayers or suspension cultures were tested for their capacity to form and grow as spheroids. Sixteen out of the 27 tested tumour cell lines formed spheroids. Nearly all of these spheroids also grew. With only two exceptions the doubling times were longer when the tumour cells grew as spheroids than when they grew in conventional mass culture. Eleven out of 13 tested human non-tumour cells formed small spheroids but of these only the spheroids of lymphoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
1
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 38 publications
2
98
1
2
Order By: Relevance
“…Observations of such an effect were initially made decades ago (Warburg, 1956), and experiments with V79 and EMT6 spheroids have shown such an effect (Freyer et al, 1984;Freyer and Sutherland, 1985). Also, necrosis has been observed in human glioma spheroids at relatively high central oxygen levels as determined by microelectrodes (Carlsson et al, 1979(Carlsson et al, , 1983. If down-regulation of oxygen consumption was coordinated at a microregional level, it might provide an explanation for the variable presence of severe hypoxia adjacent to necrosis, as indicated by nitroimidazole binding in the xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of such an effect were initially made decades ago (Warburg, 1956), and experiments with V79 and EMT6 spheroids have shown such an effect (Freyer et al, 1984;Freyer and Sutherland, 1985). Also, necrosis has been observed in human glioma spheroids at relatively high central oxygen levels as determined by microelectrodes (Carlsson et al, 1979(Carlsson et al, , 1983. If down-regulation of oxygen consumption was coordinated at a microregional level, it might provide an explanation for the variable presence of severe hypoxia adjacent to necrosis, as indicated by nitroimidazole binding in the xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…The 6 different human anaplastic thyroid carcinoma cell lines used in our study have been characterized previously: C643; 21,22 HTh 7; 23 HTh 74; 24 HTh 83; 9 and KAT-4. 25 The KAT-4 cell line was obtained from Dr. K.B.…”
Section: Cell Culturementioning
confidence: 99%
“…However, it is well known that cells growing under different environmental conditions may respond differently to specific therapeutic procedures. Factors such as nutrient supply, oxygen tension, pH and other microenvironmental conditions may affect the cellular sensitivity to paclitaxel (Carlsson et al, 1983;Mueller-Klieser, 1987). The three-dimensional arrangement of multicellular spheroids provides a cellular micromilieu that includes different environmental conditions in different parts of the spheroid, and it has been shown that spheroids from both normal and malignant tissues maintain several biochemical and morphological characteristics similar to those present in the corresponding tissue in vivo (Sutherland et al, 1986;Sutherland, 1988).…”
mentioning
confidence: 99%